Cross-Border Listings, Capital Controls, and U.S. Equity Flows to Emerging Markets - Edison, Hali (IMF Working Papers; Working Paper ;, 2003)
We analyze capital flows to emerging markets in a framework that incorporates two quantitative measures of financial integration, the intensity of capital controls and the extent of cross border listings, while controlling for traditional global (push) and country specific (pull) factors. Two important results emerge. First, the cross listing of an emerging market firm on a U.S. exchange is an important but short lived capital flows event, suggesting that the cross listed stock is in effect a new security that U.S. investors quickly bring into their portfolios. Second, the effect of financial liberalization on capital flows is more nuanced than is suggested by event studies: A reduction in capital controls results in increased inflows only when the controls are binding. Among the standard push and pull factors, global factors are important-slack U.S. economic activity is associated with increased flows to emerging markets-and U.S. investors appear to chase expected, but not past, returns.